Gustav Vigeland sculpture at the Vigeland Museum and Park in Oslo, Norway ... - Campbell, Sandy (University of Alberta Library, 2014)
Gustav Vigeland created the world's largest sculpture park by one person at Frogner in Oslo, Norway. He was born in 1869 and died in 1943. This sculpture is in the Vigeland Sculpture Park. The collection includes more than 300 sculptures. ...